The Impact Of Infographics On Digital Marketing Campaigns: Strengthening Brand Communication And Reputation - Mardian Yoel Chandra (Journal Research of Social Science, Economics, and Management, 2023)
Infographics have the ability to attract attention, provide simple explanations, simplify complex information, and help improve understanding and memory so that infographics are used as a marketing communication tool. This study aims to determine the impact of infographics on digital marketing campaigns: strengthening brand communication and reputation. This research uses a descriptive method with a qualitative approach. The qualitative approach emphasizes the meaning and understanding of the things around us, of course, which are directly related to our daily lives. The results show that infographics with their visually appealing designs and shareability on social media platforms further expand the reach and impact of marketing campaigns. By leveraging infographics, businesses can effectively convey their marketing messages, enhance brand reputation, and influence consumer behavior in a cost-effective way.